Thermal shock resistant coating, thermal insulation protective layer and preparation method and application of thermal shock resistant coating and thermal insulation protective layer
By spraying heat-proof impact coatings made of inorganic nanofiber powder and other materials on the battery pack top cover, the thermal insulation protection layer is formed, which solves the thermal insulation problem of the electric vehicle battery pack top cover when the thermal runs out of control, and improves safety and Service life.
Patent Information
- Application Number
- CN202411514291.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-27
AI Technical Summary
The top cover of the existing electric vehicle battery pack is difficult to effectively insulate heat when thermally out of control, resulting in heat conduction and fires and explosions. The existing insulation layer is prone to cracking or falling off at high temperatures, and has a short service life.
The thermal shock coating consisting of inorganic nanofiber powder, hollow glass microbeads, infrared shielding agents, binders, coupling agents, curing agents, hydrolyzing agents and diluents is used to form a thermal insulation protective layer by spraying or brushing. Combined with thermal curing technology, the mechanical properties and environmental stability of the coating are enhanced.
It achieves efficient heat insulation, prevents the transmission of heat from the battery cell to the top cover, delays the thermal runaway process, improves battery safety, and maintains the integrity and service life of the coating at high temperatures.
Smart Images

Figure CN119192889A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermal insulation materials, and in particular relates to a thermal shock resistant coating, a thermal insulation protective layer, and a preparation method and application thereof. Background Art
[0002] Battery thermal runaway is the main cause of electric vehicle safety accidents. The substrate of the top cover of the electric vehicle battery pack is usually a lightweight metal or a polymer composite material, but these materials cannot pass the fire test required for the safety of power batteries for electric vehicles. The thermal runaway reaction of the battery leads to a series of chain reactions such as decomposition of the positive electrode material, decomposition of the electrolyte, and melting of the diaphragm, releasing a large amount of heat and harmful gases. The heat is transferred from the internal battery cell to the outside and quickly affects the surrounding battery cells. The conducted heat will induce similar decomposition reactions in the adjacent battery cells, and eventually transfer the heat to the top cover of the battery pack, causing safety accidents such as fire or even explosion, making it impossible to guarantee the safety performance of electric vehicles.
[0003] At present, the industry prevents heat from being conducted outward by setting a thermal insulation layer on the outer shell of the battery pack. However, most external insulation layers have limited effects and are difficult to cope with severe thermal shocks. The related technology uses flame retardants, foaming agents and carbon-forming agents to work together to rapidly expand more than 20 times under the high temperature of the fire to block the spread of flames, which can effectively improve the safety of lithium-ion batteries in the event of a fire. However, the coating material will expand in volume at high temperatures, and its thermal expansion coefficient does not match the shell material, which will cause the coating to crack or fall off during mechanical impact, or even completely damage the internal structure of the battery, making it difficult to use for a long time and having poor practicality. Summary of the invention
[0004] The purpose of the present invention is to provide a thermal shock resistant coating, a thermal insulation protective layer and a preparation method and application thereof. The thermal shock resistant coating provided by the present invention has excellent thermal insulation performance and long-term stability.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a thermal shock resistant coating, comprising the following components in parts by weight:
[0007] 10-25 parts of inorganic nanofiber powder, 5-15 parts of hollow glass microspheres, 3-10 parts of infrared shielding agent, 15-30 parts of binder, 10-15 parts of coupling agent, 3-5 parts of curing agent, 1-2 parts of hydrolyzing agent and 1-2 parts of diluent; the inorganic nanofiber powder includes nano ceramic fiber powder and / or nano mineral fiber powder.
[0008] Preferably, the nano ceramic fiber powder includes one or more of zirconium oxide fiber powder, mullite fiber powder, silicon oxide fiber powder, aluminum oxide fiber powder, aluminum silicate fiber powder or aluminum nitride fiber powder; the nano mineral fiber powder is rock wool fiber powder; the particle size of the inorganic nano fiber powder is 20 to 70 nm.
[0009] Preferably, the inorganic nanofiber powder is obtained by grinding inorganic nanofibers; when the inorganic nanofiber powder is aluminum oxide fiber powder, silicon oxide fiber powder or zirconium oxide fiber powder, the method for preparing the inorganic nanofibers comprises the following steps:
[0010] Mixing an inorganic powder, a dispersant and a polymer solution to obtain a spinning solution; the inorganic powder is aluminum oxide, silicon oxide or zirconium oxide;
[0011] The spinning solution is subjected to air-draw spinning to obtain spun fibers;
[0012] The spun fibers are sintered to obtain the inorganic nanofibers.
[0013] Preferably, the hollow glass microspheres have a particle size of less than 200 mesh, a wall thickness of 0.5 to 2 μm, and a density of 0.6 to 1 g / cm 3 ;
[0014] The infrared shielding agent includes one or more of titanium dioxide, silicon carbide and carbon powder;
[0015] The binder includes an inorganic binder and an organic binder; the inorganic binder includes one or more of alumina, sodium silicate, potassium silicate, sodium aluminate and calcium aluminate; the organic binder includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and butyl acrylate;
[0016] The coupling agent is a silane coupling agent;
[0017] The curing agent is an organic peroxide;
[0018] The hydrolyzing agent is an organic acid;
[0019] The diluent is an organic solvent.
[0020] The present invention also provides a method for preparing the thermal shock resistant coating according to the above technical solution, comprising the following steps:
[0021] Mixing inorganic nanofiber powder, hollow glass microspheres and infrared shielding agent to obtain powder;
[0022] Mixing a binder, a coupling agent, a curing agent, a hydrolyzing agent and a diluent to obtain a liquid material;
[0023] The powder material and the liquid material are mixed to obtain the thermal shock resistant coating.
[0024] The present invention also provides a heat-insulating protective layer, which is a coating formed by the heat-resistant shock coating described in the above technical solution or the heat-resistant shock coating obtained by the preparation method described in the above technical solution.
[0025] Preferably, the thickness of the thermal insulation protective layer is 500-1000 μm.
[0026] The present invention also provides a method for preparing the heat-insulating protective layer described in the above technical solution, comprising the following steps:
[0027] The heat-shock-resistant coating is coated on the surface of the substrate and thermally cured to obtain the heat-insulating protective layer.
[0028] Preferably, the coating method is brushing or spraying; the coating thickness is 1 to 2 mm;
[0029] The temperature of the thermal curing is 80-150° C. and the time is 30-60 minutes.
[0030] The present invention also provides the use of the thermal shock resistant coating described in the above technical solution, the thermal shock resistant coating obtained by the preparation method described in the above technical solution, the thermal insulation protective layer described in the above technical solution or the thermal insulation protective layer obtained by the preparation method described in the above technical solution in a battery.
[0031] The present invention provides a heat shock resistant coating, comprising the following components in parts by mass: 10-25 parts of inorganic nanofiber powder, 5-15 parts of hollow glass microspheres, 3-10 parts of infrared shielding agent, 15-30 parts of binder, 10-15 parts of coupling agent, 3-5 parts of curing agent, 1-2 parts of hydrolyzing agent and 1-2 parts of diluent; the inorganic nanofiber powder comprises nano-ceramic fiber powder and / or nano-ore fiber powder. The heat shock resistant coating provided by the present invention uses nano-ceramic fiber powder and / or nano-ore fiber powder as the key components of the coating, giving the coating extremely low thermal conductivity and good mechanical properties, and the ratio of auxiliary components such as binder and coupling agent further improves the interface bonding force between the fiber and the substrate, enhances the comprehensive mechanical properties and environmental stability of the coating, and also plays a decisive role in the thermal insulation performance of the coating. The thermal shock resistant coating is a new type of thermal shock resistant coating with excellent thermal insulation performance, strong bonding with the substrate, high temperature resistance, and long-term use. When applied on the surface of the battery pack top cover, it will form a thermal insulation protective layer, which can slow down and block the heat transfer of the top cover, effectively prevent the heat of the battery cell from transferring to the top cover, prevent high-temperature and high-pressure gas from burning through the metal or composite material top cover, and delay the thermal runaway process of the internal battery cell. In the case of tram accidents, it increases the time for the thermal runaway of the power battery to spread to the passenger compartment, avoids harmful smoke and gas directly endangering the safety of passengers, buys precious time for passenger escape, vehicle cooling and rescue, and can also minimize the harm and impact of the accident, ultimately achieving the purpose of improving the safety of new energy vehicles. At the same time, the thermal shock resistant coating is also characterized by high cost performance and simple spraying process. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0033] Figure 1 This is a schematic diagram of the sequence of initiation of thermal runaway of a battery pack;
[0034] Figure 2 A schematic diagram of the position of the thermal shock resistant coating provided in an embodiment of the present invention when applied in a battery;
[0035] Figure 3 A flow chart of the preparation method of the heat-shock-resistant coating and the heat-insulating protective layer provided by the present invention;
[0036] Figure 4 This is a physical picture of the heat shock resistant coating material obtained in Example 1 after being dried at room temperature and thermally cured;
[0037] Figure 5The front and back of the thermal shock resistant coating sample obtained in Example 2 were subjected to ablation performance test;
[0038] Figure 6 This is a physical comparison diagram of the thermal shock resistant coating sample obtained in Example 2 before and after the ablation test. DETAILED DESCRIPTION
[0039] The present invention provides a thermal shock resistant coating, comprising the following components in parts by weight:
[0040] 10-25 parts of inorganic nanofiber powder, 5-15 parts of hollow glass microspheres, 3-10 parts of infrared shielding agent, 15-30 parts of binder, 10-15 parts of coupling agent, 3-5 parts of curing agent, 1-2 parts of hydrolyzing agent and 1-2 parts of diluent; the inorganic nanofiber powder includes nano ceramic fiber powder and / or nano mineral fiber powder.
[0041] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.
[0042] In the present invention, the thermal shock resistant coating includes 10 to 25 parts by mass of inorganic nanofiber powder. In a specific embodiment, the mass fraction of the inorganic nanofiber powder can be 10 parts, 15 parts, 20 parts or 25 parts; the nano-ceramic fiber powder preferably includes one or more of zirconium oxide fiber powder, mullite fiber powder, silica fiber powder, alumina fiber powder, aluminum silicate fiber powder or aluminum nitride fiber powder. In a specific embodiment, the nano-ceramic fiber powder can be silica fiber powder, alumina fiber powder or zirconium oxide fiber powder; the nano-ore fiber powder is preferably rock wool fiber powder; the particle size of the inorganic nanofiber powder is preferably 20 to 70 nm. In a specific embodiment, the particle size of the inorganic nanofiber powder can be 20 nm, 50 nm or 70 nm. The inorganic nanofibers used in the present invention can be normally used at 800-1200°C, such as the temperature range of silicon dioxide nanofibers is 1000-1200°C, the temperature range of aluminum oxide nanofibers is 1200-1600°C, and the temperature range of zirconium oxide nanofibers is 1200-2400°C.
[0043] In the present invention, the inorganic nanofiber powder is preferably obtained by grinding inorganic nanofibers. The grinding is used to reduce the particle size to improve the uniformity of the coating.
[0044] In the present invention, when the inorganic nanofiber powder is aluminum oxide fiber powder, silicon oxide fiber powder or zirconium oxide fiber powder, the method for preparing the inorganic nanofiber preferably comprises the following steps:
[0045] Mixing an inorganic powder, a dispersant and a polymer solution to obtain a spinning solution; the inorganic powder is aluminum oxide, silicon oxide or zirconium oxide;
[0046] The spinning solution is subjected to air-draw spinning to obtain spun fibers;
[0047] The spun fibers are sintered to obtain the inorganic nanofibers.
[0048] The present invention mixes inorganic powder, ceramic dispersant and polymer solution to obtain spinning solution. The dispersant preferably includes Tween-80 and ammonia water; the mass percentage of the ceramic dispersant in the spinning solution is preferably 1% to 5%; the polymer solution preferably includes polyacrylic acid, polymethacrylic acid, methyl cellulose, polyacrylic acid ammonium salt, polymethacrylic acid ammonium salt, polyvinyl alcohol, polyethylene glycol and polyperfluorosulfonic acid; the pH value of the polyacrylic acid ammonium salt is preferably 7; the pH value of the polymethacrylic acid ammonium salt is preferably 7; the solid content of the polymer solution is preferably 40% to 50%; the mass percentage of the polymer solution in the spinning solution is preferably 30% to 40%; the function of the dispersant and the polymer solution is to enhance the dispersibility of the inorganic powder.
[0049] After obtaining the spinning solution, the present invention performs airflow traction spinning on the spinning solution to obtain spun fibers. In the present invention, the airflow traction spinning equipment preferably includes a container, a closed-loop nylon line, and a gas pipeline perpendicular to the nylon line; the role of the nylon line is that the nylon line is wrapped by the spinning solution due to the specific viscosity of the spinning solution and the wettability with nylon. The air pressure of the airflow traction spinning is preferably 0.1-0.3MPa. In a specific embodiment, the air pressure of the airflow traction spinning can be 0.1MPa, 0.2MPa or 0.3MPa; the jet flow rate is preferably 20-25m / s; the nozzle diameter is preferably 1.2-1.8mm, in a specific embodiment, the nozzle diameter can be 1.2mm, 1.6mm or 1.8mm; the height difference between the collecting plate and the nozzle is preferably 25-30cm, in a specific embodiment, the height difference between the collecting plate and the nozzle can be 25cm, 27cm or 30cm. The present invention adopts air spinning to stretch the polymer solution mainly by high-speed airflow. When the liquid flows to the collector, the solvent evaporates rapidly to form a dry fiber material. Air spinning has faster production speed, no need for high voltage, better safety, simpler process, applicable to a wider range of solution systems, controllable fiber structure and diameter, and environmental friendliness, making it superior to electrostatic spinning technology.
[0050] After obtaining the spun fibers, the present invention sinters the spun fibers to obtain the inorganic nanofibers. The sintering process preferably also includes cutting; the sintering temperature is preferably 500-600°C, and in a specific embodiment, the sintering temperature can be 500°C, 550°C or 600°C; the time is preferably 3-6h, and in a specific embodiment, the time can be 3h, 4h or 6h; the average diameter of the inorganic nanofibers is preferably 20-70nm, and in a specific embodiment, the average diameter of the inorganic nanofibers can be 20nm, 50nm or 70nm. The sintering process is to remove the dispersant and polymer, enhance the bonding force between the fibers, and form ceramic nanofibers with good mechanical properties.
[0051] Based on the mass fraction of the inorganic nanofiber powder, the thermal shock resistant coating includes 5 to 15 parts of hollow glass microspheres. In a specific embodiment, the mass fraction of the hollow glass microspheres can be 5, 10 or 15 parts. The particle size of the hollow glass microspheres can be less than 200 meshes. The wall thickness can be 0.5 to 2 μm. In a specific embodiment, it can be 1 μm. The density can be 0.6 to 1 g / cm 3 In a specific embodiment, it can be 0.8 g / cm 3 The hollow glass microspheres are used to increase the heat insulation performance of the coating and reduce heat conduction.
[0052] Based on the mass fraction of the inorganic nanofiber powder, the thermal shock resistant coating includes 3 to 10 parts of infrared shielding agent. In a specific embodiment, the mass fraction of the infrared shielding agent can be 3 parts, 5 parts or 10 parts; the infrared shielding agent preferably includes one or more of titanium dioxide, silicon carbide and carbon powder. In a specific embodiment, the infrared shielding agent is titanium dioxide, silicon carbide or carbon powder.
[0053] Based on the mass fraction of the inorganic nanofiber powder, the heat shock resistant coating includes 15 to 30 parts of a binder. In a specific embodiment, the mass fraction of the binder can be 15, 25 or 30 parts; the binder preferably includes an inorganic binder and an organic binder; the inorganic binder preferably includes one or more of aluminum oxide, sodium silicate, potassium silicate, sodium aluminate and calcium aluminate. In a specific embodiment, the inorganic binder can be sodium silicate, potassium silicate or sodium aluminate; the organic binder preferably includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and butyl acrylate. In a specific embodiment, the organic binder can be polyvinyl alcohol, sodium carboxymethyl cellulose or butyl acrylate; the mass ratio of the inorganic binder to the organic binder is preferably 2 to 10:1. In a specific embodiment, the mass ratio of the inorganic binder to the organic binder can be 2:1, 6:1 or 10:1. In the present invention, the inorganic binder is generally resistant to high temperatures, but the shrinkage degree is large when drying, and the coating is easy to crack. Organic binders usually have film-forming properties, but poor temperature resistance. Therefore, the effective combination of the two materials can not only give full play to the high temperature resistance of the inorganic binder, but also take advantage of the good film-forming property of the organic binder to obtain excellent performance of the coating. However, when the amount of organic binder is large, the coating will produce a strong odor at high temperature and turn yellow after heating. Therefore, when the ratio of organic to inorganic binders is controlled within the above range, the coating will not turn yellow, and there will be no odor at high temperature, which has no impact on the environment.
[0054] Based on the mass fraction of the inorganic nanofiber powder, the heat-resistant shock coating includes 10 to 15 parts of a coupling agent. In a specific embodiment, the mass fraction of the coupling agent can be 10 parts, 12 parts or 15 parts; the coupling agent is preferably a silane coupling agent; the silane coupling agent is preferably one or more of γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane, γ-glycidyloxypropyl trimethoxysilane and γ-aminopropyl trimethoxysilane. In a specific embodiment, the silane coupling agent can be γ-aminopropyl triethoxysilane, γ-methacryloxypropyl trimethoxysilane or γ-glycidyloxypropyl trimethoxysilane. The present invention adds a coupling agent to the coating formula to improve the interface bonding force between the inorganic fiber and the substrate, and enhance the comprehensive mechanical properties and environmental stability of the coating.
[0055] Based on the mass fraction of the inorganic nanofiber powder, the heat-resistant shock resistant coating includes 3 to 5 parts of a curing agent. In a specific embodiment, the mass fraction of the curing agent can be 3 parts, 4 parts or 5 parts; the curing agent is preferably an organic peroxide; the organic peroxide preferably includes one or more of benzoyl peroxide, tert-butyl peroxide, dicumyl peroxide and diisopropyl perphthalate. In a specific embodiment, the curing agent can be benzoyl peroxide, tert-butyl peroxide or diisopropyl perphthalate.
[0056] Based on the mass fraction of the inorganic nanofiber powder, the thermal shock resistant coating includes 1 to 2 parts of a hydrolyzing agent. In a specific embodiment, the mass fraction of the hydrolyzing agent can be 1 part, 1.5 parts or 2 parts; the hydrolyzing agent is preferably an organic acid; the organic acid is preferably glacial acetic acid; the pH value of the glacial acetic acid is preferably 3.2 to 3.4. In a specific embodiment, the pH value of the glacial acetic acid can be 3.2 or 3.4.
[0057] Based on the mass fraction of the inorganic nanofiber powder, the thermal shock resistant coating includes 1 to 2 parts of a diluent. In a specific embodiment, the mass fraction of the diluent can be 1 part, 1.5 parts or 2 parts; the diluent is preferably an organic solvent; the organic solvent is preferably ethanol. In a specific embodiment, the diluent can be anhydrous ethanol; the mass ratio of the hydrolyzing agent, the silane coupling agent and the diluent is preferably 1 to 2:10 to 15:1 to 2. In a specific embodiment, the mass ratio of the hydrolyzing agent, the silane coupling agent and the diluent can be 1.5:10:1.
[0058] Figure 1 This is a schematic diagram of the sequence of thermal runaway initiation of the battery pack. Figure 1 It can be seen that during the battery thermal runaway process, the heat generated by the initial faulty battery cell will quickly spread to the adjacent battery cells through heat conduction, thermal radiation, etc., triggering a cascade reaction, causing the battery pack as a whole to release high-temperature and high-pressure gas, burn through the metal or composite top cover, and ultimately cause a fire in the entire vehicle.
[0059] The heat-resistant shock coating provided by the present invention uses nano-ceramic fiber powder and / or nano-mineral fiber powder as the key components of the coating, which gives the coating extremely low thermal conductivity and good mechanical properties. The ratio of auxiliary components such as binders and coupling agents further improves the interfacial bonding between the fiber and the substrate, enhances the comprehensive mechanical properties and environmental stability of the coating, and also plays a decisive role in the thermal insulation performance of the coating. In addition, the ceramic nanofibers in the coating occupy a small space, have a small weight, and have thermal insulation performance far exceeding that of mica boards in related technologies, and the spraying process is simple. The heat-resistant shock coating is a new type of heat-resistant shock coating with excellent thermal insulation performance, firm bonding with the substrate, high temperature resistance, and long-term use.
[0060] The present invention also provides a method for preparing the thermal shock resistant coating according to the above technical solution, comprising the following steps:
[0061] Mixing inorganic nanofiber powder, hollow glass microspheres and infrared shielding agent to obtain powder;
[0062] Mixing a binder, a coupling agent, a curing agent, a hydrolyzing agent and a diluent to obtain a liquid material;
[0063] The powder material and the liquid material are mixed to obtain the thermal shock resistant coating.
[0064] In the present invention, the mixing is preferably stirring; the stirring device is preferably a magnetic stirrer; the present invention does not have any special restrictions on the rotation speed and time of the stirring, and the heat shock resistant coating can be mixed evenly in a manner well known to those skilled in the art.
[0065] The present invention also provides a heat-insulating protective layer, which is a coating formed by the heat-resistant shock coating described in the above technical solution or the heat-resistant shock coating obtained by the preparation method described in the above technical solution.
[0066] In the present invention, the thickness of the thermal insulation protective layer is preferably 500-1000 μm. In a specific embodiment, the thickness of the thermal insulation protective layer may be 500 μm, 800 μm or 1000 μm.
[0067] The present invention also provides a method for preparing the heat-insulating protective layer described in the above technical solution, comprising the following steps:
[0068] The heat-shock-resistant coating is coated on the surface of the substrate and thermally cured to obtain the heat-insulating protective layer.
[0069] In the present invention, the coating process preferably also includes cleaning and polishing in sequence; the cleaning and polishing process is to ensure that the surface of the battery pack top cover is clean, dry, and oil-free, to increase the roughness of the substrate, and to enhance the adhesion of the coating.
[0070] In the present invention, the coating method is preferably brushing or spraying; the spraying air pressure is preferably 2-3.5 Bar or 30-50 psi, and in a specific embodiment, the spraying air pressure can be 2 Bar, 2.5 Bar or 3.5 Bar; the spraying caliber is preferably 1.2-1.8 mm, and in a specific embodiment, the spraying caliber can be 1.2 mm, 1.6 mm or 1.8 mm; the spraying distance is preferably 25-30 cm; the number of coatings is preferably 2-3 times; the thickness is preferably 1-2 mm, and in a specific embodiment, the coating thickness can be 1 mm, 1.5 mm or 2 mm; each spraying preferably also includes drying; the drying is preferably natural drying, and the time is preferably 15-30 min, and in a specific embodiment, the drying time can be 15 min, 20 min or 30 min.
[0071] In the present invention, the temperature of the thermal curing is preferably 80-150°C, and the time is preferably 30-60 minutes; in a specific embodiment, the thermal curing may include a first stage and a second stage; the temperature of the first stage may be 80°C or 100°C, and the time may be 15 minutes, 20 minutes or 30 minutes; the temperature of the second stage may be 130°C or 150°C, and the time may be 15 minutes, 20 minutes or 30 minutes. The effect of the thermal curing is that during the thermal curing process, the components (such as resin) in the coating will undergo a cross-linking reaction to form a three-dimensional network structure, thereby improving the mechanical strength of the coating; through thermal curing, the molecular structure of the coating becomes more stable, and is not easily eroded by environmental factors such as chemicals, ultraviolet rays, and moisture, thereby extending the service life of the coating; it can improve the adhesion between the coating and the substrate, and prevent the coating from peeling or falling off during use; ensure that the coating material is uniformly cured, so that it has consistent thermal insulation properties on the entire surface; thermal curing can significantly shorten the curing time of the coating compared to room temperature drying; high temperature helps to participate in the volatilization of the solvent, reduce the residual organic volatiles in the coating, and improve the environmental performance of the coating.
[0072] The preparation method of the heat-insulating protective layer provided by the present invention adopts a process route of first spraying or brushing and then curing to form a film, which gives the coating a uniform and dense structure and controls a reasonable coating thickness, which is the key to achieving excellent performance of the coating.
[0073] The present invention also provides the use of the thermal shock resistant coating described in the above technical solution, the thermal shock resistant coating obtained by the preparation method described in the above technical solution, the thermal insulation protective layer described in the above technical solution or the thermal insulation protective layer obtained by the preparation method described in the above technical solution in a battery.
[0074] In the present invention, the thermal shock resistant coating or thermal insulation protective layer is preferably applied to the top cover of the battery pack; the present invention does not have any special limitation on the process of applying the thermal shock resistant coating or thermal insulation protective layer to the battery, and the process familiar to those skilled in the art can be used.
[0075] The present invention applies heat-shock-resistant coating and heat-insulating protective layer to the battery. When coated on the surface of the battery pack top cover, a heat-insulating protective layer is formed, which can slow down and block the heat transfer of the top cover, effectively prevent the heat of the battery core from being transferred to the top cover, prevent high-temperature and high-pressure gas from burning through the metal or composite material top cover, delay the thermal runaway process of the internal battery core, increase the time for the thermal runaway of the power battery to spread to the passenger compartment in the tram accident, avoid harmful smoke gas directly endangering the safety of passengers, buy precious time for passenger escape, vehicle cooling and rescue, and also minimize the harm and impact of the accident, ultimately achieving the purpose of improving the safety of new energy vehicles. At the same time, the heat-resistant shock coating also has the characteristics of high cost performance and simple spraying process.
[0076] In order to further illustrate the present invention, the thermal shock resistant coating, thermal insulation protective layer, preparation method and application thereof provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0077] Figure 2 A schematic diagram of the position of the thermal shock resistant coating provided in an embodiment of the present invention applied in a battery, wherein the thermal shock resistant coating forms a thermal insulation protective layer on the top cover of the battery pack.
[0078] Figure 3 This is a flow chart of the preparation method corresponding to the thermal shock resistant coating and thermal insulation protective layer provided by the present invention, and the specific steps are as described in Examples 1 to 3.
[0079] Example 1
[0080] The raw materials used in this embodiment are ceramic nanofiber powder, hollow glass microspheres, infrared shielding agent, binder, curing agent, hydrolyzing agent, silane coupling agent and diluent, among which the ceramic nanofiber powder is silicon dioxide ceramic nanofiber powder; the infrared shielding agent is silicon carbide; the binder includes an inorganic binder and an organic binder; the inorganic binder is sodium silicate; the organic binder is polyvinyl alcohol; the curing agent is benzoyl peroxide; the hydrolyzing agent is glacial acetic acid with a pH of 3.2; the silane coupling agent is γ-aminopropyltriethoxysilane; and the diluent is anhydrous ethanol.
[0081] Mix silica ceramic nanofiber powder with a particle size of 70nm, hollow glass microspheres and silicon carbide to prepare powder; fully stir sodium silicate, polyvinyl alcohol, benzoyl peroxide, glacial acetic acid, γ-aminopropyl triethoxysilane and anhydrous ethanol to prepare liquid; mix the powder and liquid, and fully stir them with a magnetic stirrer to prepare a coating slurry. Among them, 20 parts of silica ceramic nanofiber powder, 10 parts of hollow glass microspheres, 5 parts of silicon carbide, 15 parts of sodium silicate, 2 parts of polyvinyl alcohol, 3 parts of benzoyl peroxide, 1 part of glacial acetic acid with a pH of 3.2, 10 parts of γ-aminopropyl triethoxysilane, and 2 parts of anhydrous ethanol.
[0082] Ensure that the surface of the battery pack top cover is clean, dry, and free of oil, and polish it with sandpaper. Spray the coating on the surface of the battery pack top cover for the first time. The spraying air pressure is 2 Bar, the spraying diameter is 1.8 mm, the spraying distance is 30 cm, the spraying thickness is 1 mm, and it is dried at room temperature for 20 minutes. After drying, spray a second time with a spraying thickness of 1 mm, dry at room temperature for 20 minutes, and perform heat treatment. The heat treatment specifically includes: placing the dried battery pack top cover coating material into an oven, keeping it at 80°C for 30 minutes, then heating it to 150°C and keeping it for 30 minutes, slowly cooling it and taking it out to obtain a heat shock resistant coating material with a thickness of 500 μm. See the actual picture of the obtained heat shock resistant coating material after room temperature drying and heat curing. Figure 4 .
[0083] Depend on Figure 4 It can be seen that the coating is sprayed on the surface of the substrate, dried at room temperature and heat-treated to form a thermal shock resistant coating that evenly covers the substrate.
[0084] Example 2
[0085] The raw materials used in this embodiment are nano-ceramic fiber powder, hollow glass microspheres, infrared shielding agent, binder, curing agent, hydrolyzing agent, silane coupling agent and diluent, among which the nano-ceramic fiber powder is alumina nano-ceramic fiber powder; the infrared shielding agent is titanium dioxide; the binder includes an inorganic binder and an organic binder; the inorganic binder is sodium aluminate; the organic binder is sodium carboxymethyl cellulose; the curing agent is tert-butyl peroxide; the hydrolyzing agent is glacial acetic acid with a pH of 3.2; the silane coupling agent is γ-methacryloxypropyltrimethoxysilane; and the diluent is anhydrous ethanol.
[0086] 60g of alumina ceramic powder is mixed with a ceramic dispersant and a polymer solution to obtain a spinning solution, wherein the ceramic dispersant is 2g of Tween-80, and the polymer solution is a polyacrylic acid solution prepared by mixing 15g of polyacrylic acid with 20g of water.
[0087] The obtained dispersion is transferred to a syringe and sent to the spinneret of the air spinning equipment through a gear pump. The spinning system is assembled by a container containing a spinning solution, a closed-loop nylon line, and a gas pipeline arranged perpendicular to the line for providing high-speed air blowing. The spinning solution is continuously carried out via a circulating nylon line passing through the container. A continuous air supply is provided using an air compressor. The nozzle diameter of the spinneret is 1.6mm, and the air flow generator is started to generate a high-speed air flow. The air pressure is 0.3MPa, the jet flow rate is 25m / s, and the high-speed air flow sprays the dispersion. The solution is formed into a Taylor cone and sprayed at high speed. Nanofibers are formed by rapid stretching and swinging, and the solvent is evaporated. The fibers are collected on a collector about 30cm away from the spinning point, and the average diameter of the obtained fibers is 70nm. The collected fiber web is cut and the fibers are sintered in an air atmosphere at 600℃ for 6h to obtain alumina ceramic nanofibers. The cut alumina ceramic nanofibers are ground to obtain alumina ceramic nanofiber powder.
[0088] Alumina ceramic nanofiber powder with a particle size of 70nm, hollow glass microspheres and titanium dioxide are mixed to prepare a powder; sodium aluminate, sodium carboxymethyl cellulose, tert-butyl peroxide, glacial acetic acid, γ-methacryloxypropyl trimethoxysilane and anhydrous ethanol are fully stirred to prepare a liquid; the powder and the liquid are mixed, and a coating slurry is prepared after being fully stirred by a magnetic stirrer. Among them, 20 parts of alumina ceramic nanofiber powder, 10 parts of hollow glass microspheres, 10 parts of titanium dioxide, 15 parts of sodium aluminate, 2 parts of sodium carboxymethyl cellulose, 4 parts of tert-butyl peroxide, 1 part of glacial acetic acid with a pH of 3.2, 12 parts of γ-methacryloxypropyl trimethoxysilane, and 2 parts of anhydrous ethanol.
[0089] Ensure that the surface of the battery pack top cover is clean, dry, and free of oil, and polish it with sandpaper. Spray the paint onto the surface of the battery pack top cover for the first time. The spraying air pressure is 2 Bar, the spraying diameter is 1.8 mm, the spraying distance is 25 cm, the spraying thickness is 1 mm, and it is dried at room temperature for 20 minutes. After drying, spray a second time with a spraying thickness of 1 mm, dry at room temperature for 20 minutes, and perform heat treatment. The heat treatment specifically includes: putting the dried battery pack top cover coating material into an oven, keeping it at 80°C for 30 minutes, then heating it to 150°C for 30 minutes, slowly cooling it down and taking it out to obtain a heat shock resistant coating material with a thickness of 800 μm.
[0090] Example 3
[0091] The raw materials used in this embodiment are nano-ceramic fiber powder, hollow glass microspheres, infrared shielding agent, binder, curing agent, hydrolyzing agent, silane coupling agent and diluent, wherein the nano-ceramic fiber powder is zirconium oxide nano-ceramic fiber powder; the infrared shielding agent is carbon powder; the binder includes an inorganic binder and an organic binder; the inorganic binder is potassium silicate; the organic binder is butyl acrylate; the curing agent is diisopropyl peroxy terephthalate; the hydrolyzing agent is glacial acetic acid with a pH of 3.2; the silane coupling agent is γ-glycidyloxypropyltrimethoxysilane; and the diluent is anhydrous ethanol.
[0092] Mix zirconia ceramic nanofiber powder with a particle size of 50 mm, hollow glass microspheres and carbon powder to prepare powder; fully stir potassium silicate, butyl acrylate, diisopropyl perterephthalate, glacial acetic acid, γ-glycidyloxypropyl trimethoxysilane and anhydrous ethanol to prepare liquid; mix the powder and liquid, and fully stir them with a magnetic stirrer to prepare a coating slurry. 25 parts of zirconia ceramic nanofiber powder, 15 parts of hollow glass microspheres, 3 parts of titanium dioxide, 20 parts of potassium silicate, 2 parts of butyl acrylate, 5 parts of diisopropyl perterephthalate, 1 part of glacial acetic acid with a pH of 3.2, 15 parts of γ-glycidyloxypropyl trimethoxysilane, and 2 parts of anhydrous ethanol.
[0093] Ensure that the surface of the battery pack top cover is clean, dry, and free of oil, and polish it with sandpaper. Spray the paint onto the surface of the battery pack top cover for the first time. The spraying air pressure is 3.5 Bar, the spraying diameter is 1.2 mm, the spraying distance is 25 cm, the spraying thickness is 1 mm, and it is dried at room temperature for 25 minutes. After drying, spray a second time with a spraying thickness of 1 mm, dry at room temperature for 25 minutes, and perform heat treatment. The heat treatment specifically includes: putting the dried battery pack top cover coating material into an oven, keeping it at 80°C for 30 minutes, then heating it to 150°C for 30 minutes, slowly cooling it down and taking it out to obtain a heat shock resistant coating material with a thickness of 1000 μm.
[0094] Test Example 1
[0095] The thermal conductivity and thermal shock resistance of the thermal shock resistant coating materials obtained in Examples 1 to 3 were tested.
[0096] The thermal conductivity test is carried out using the flat plate method. The sample is clamped between the heating plate and the cooling plate to ensure good contact between the sample and the plate. Thermal conductive paste is used to reduce contact thermal resistance. The heating plate temperature is set to 100°C and the cooling plate temperature is set to 25°C. The heating time is set to 2h. The system reaches a steady state and the temperature gradient and heat flow are ensured to be stable. Finally, the data is obtained and the thermal conductivity of the sample is calculated according to Fourier's theorem.
[0097] The thermal shock resistance test is carried out by the thermal cycle method. The sample is placed in a high-temperature furnace, heated to 1000°C, and maintained for 15 minutes to ensure uniform temperature inside the sample; the sample is quickly removed from the furnace and immediately placed in liquid nitrogen for cooling, so that it quickly cools to a low temperature; the heating and cooling cycles are repeated 20 times; after all the predetermined thermal cycles are completed, the sample is inspected in detail, the crack conditions are recorded, and the thermal shock resistance of the sample is evaluated.
[0098] The test results are shown in Table 1.
[0099] Table 1 Thermal conductivity and thermal shock resistance data of thermal shock resistant coating materials obtained in Examples 1 to 3
[0100] Example Thermal conductivity Thermal shock resistance Embodiment 1 0.038W / m·K >20 times, no cracks Embodiment 2 0.031W / m·K >20 times, no cracks Embodiment 3 0.023W / m·K >20 times, no cracks
[0101] It can be seen from Table 1 that the thermal shock resistant coating materials obtained in Examples 1 to 3 all have extremely low thermal conductivity and excellent thermal shock resistance.
[0102] Test Example 2
[0103] The thermal shock resistant coating sample obtained in Example 2 was subjected to ablation performance test. During the ablation process, the temperature of the front side of the substrate can reach 1500°C, and the temperature of the back side can reach 500°C. See the front and back side pictures for details. Figure 5 , the actual comparison pictures before and after ablation are shown in Figure 6 .
[0104] Depend on Figures 5-6 It can be seen that the coating has excellent thermal insulation and ablation resistance. It still has excellent thermal insulation performance under high-temperature ablation of 1500°C. After 15 minutes of high-temperature ablation, the back temperature is only 500°C. The coating has no cracks after 20 thermal shock tests and the base material will not melt.
[0105] It can be seen from the above embodiments that the present invention adopts ceramic nanofibers as the main raw material, and through reasonable formula design and preparation process, prepares a coating with extremely low thermal conductivity and excellent mechanical properties, and applies it to the thermal shock protection of the battery pack top cover, thereby solving the problem that the top cover of the prior art is easily damaged by heat.
[0106] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A thermal shock resistant coating, characterized in that: The composition includes the following components in parts by weight: 10-25 parts of inorganic nanofiber powder, 5-15 parts of hollow glass microspheres, 3-10 parts of infrared shielding agent, 15-30 parts of binder, 10-15 parts of coupling agent, 3-5 parts of curing agent, 1-2 parts of hydrolyzing agent and 1-2 parts of diluent; the inorganic nanofiber powder includes nano ceramic fiber powder and / or nano mineral fiber powder.
2. The thermal shock resistant coating according to claim 1, characterized in that: The nano ceramic fiber powder includes one or more of zirconium oxide fiber powder, mullite fiber powder, silicon oxide fiber powder, aluminum oxide fiber powder, aluminum silicate fiber powder or aluminum nitride fiber powder; the nano mineral fiber powder is rock wool fiber powder; the particle size of the inorganic nano fiber powder is 20 to 70 nm.
3. The thermal shock resistant coating according to claim 1 or 2, characterized in that: The inorganic nanofiber powder is obtained by grinding inorganic nanofibers; when the inorganic nanofiber powder is aluminum oxide fiber powder, silicon oxide fiber powder or zirconium oxide fiber powder, the preparation method of the inorganic nanofibers comprises the following steps: Mixing an inorganic powder, a dispersant and a polymer solution to obtain a spinning solution; the inorganic powder is aluminum oxide, silicon oxide or zirconium oxide; The spinning solution is subjected to air flow spinning to obtain spun fibers; The spun fibers are sintered to obtain the inorganic nanofibers.
4. The thermal shock resistant coating according to claim 1, characterized in that: The hollow glass microspheres have a particle size of less than 200 mesh, a wall thickness of 0.5 to 2 μm, and a density of 0.6 to 1 g / cm 3 ; The infrared shielding agent includes one or more of titanium dioxide, silicon carbide and carbon powder; The binder includes an inorganic binder and an organic binder; the inorganic binder includes one or more of alumina, sodium silicate, potassium silicate, sodium aluminate and calcium aluminate; the organic binder includes one or more of polyvinyl alcohol, sodium carboxymethyl cellulose and butyl acrylate; The coupling agent is a silane coupling agent; The curing agent is an organic peroxide; The hydrolyzing agent is an organic acid; The diluent is an organic solvent.
5. The method for preparing the thermal shock resistant coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: Mixing inorganic nanofiber powder, hollow glass microspheres and infrared shielding agent to obtain powder; Mixing a binder, a coupling agent, a curing agent, a hydrolyzing agent and a diluent to obtain a liquid material; The powder material and the liquid material are mixed to obtain the thermal shock resistant coating.
6. A heat-insulating protective layer, characterized in that: The thermal insulation protective layer is a coating formed by the thermal shock resistant coating according to any one of claims 1 to 4 or the thermal shock resistant coating obtained by the preparation method according to claim 5.
7. The heat-insulating protective layer according to claim 6, characterized in that: The thickness of the heat-insulating protective layer is 500-1000 μm.
8. The method for preparing the heat-insulating protective layer according to claim 6 or 7, characterized in that: The following steps are involved: The heat-shock-resistant coating is coated on the surface of the substrate and thermally cured to obtain the heat-insulating protective layer.
9. The preparation method according to claim 8, characterized in that: The coating method is brushing or spraying; the coating thickness is 1 to 2 mm; The temperature of the thermal curing is 80-150° C. and the time is 30-60 minutes.
10. Use of the thermal shock resistant coating according to any one of claims 1 to 4, the thermal shock resistant coating obtained by the preparation method according to claim 5, the thermal insulation protective layer according to claim 6 or 7, or the thermal insulation protective layer obtained by the preparation method according to claim 8 or 9 in batteries.
Citation Information
Patent Citations
Fiber-reinforced high-temperature-resistant thermal insulation and heat preserving ceramic coating and preparation method thereof
CN102464933A
Organic / inorganic composite heat insulation coating and preparation method thereof
CN107746590A
Packaging coating for fireproof and heat-insulating aerogel gasket of power battery cell and application of packaging coating
CN118308008A
